207 The Interplay Between the Renin Angiotensin System and Pacing Postconditioning Induced Cardiac Protection. (3rd June 2016) - Babiker, Fawzi; Al-Jarallah, Aishah; Joseph, Shaji
Abstract : Background: Accumulating evidence suggests a cardioprotective role of pacing postconditioning (PPC). The interaction between RAS and PPC induced cardiac protection is however not clearly understood. The role of angiotensin converting enzyme (ACE), Angtiosin II (Ang II) and angiotensin receptor 1 (AT1) remains to be identified. Objective: The objective of this study was therefore to investigate the role of ACE-Ang II-AT1 axes of RAS in the protective effects of PPC. Methods: The role of RAS was tested by infusion of Ang II, chymostatin (inhibitor of locally produced Ang II), ACE blocker (captopril) and AT1 antagonist (irbesartan). Hemodynamics data was computed digitally and infarct size was determined using 2, 3, 5-Triphenyltetrazolium chloride (TTC) staining and by measuring creatine kinase (CK) and lactate dehydrogenase (LDH) levels. Results: In comparison to hearts subjected to I/R injury or untreated control hearts, PPC significantly (P < 0.001) improved cardiac hemodynamics and reduced infarct size and cardiac enzymes. Systemic infusions of Ang II did not affect I/R injury or PPC mediated protection. Nonetheless inhibition of endogenously synthesised Ang II protected against I/R induced cardiac damage and did not block or augment the protective effects of PPC. The administration of AT1 antagonist did not alleviate I/R induced damage. Interestingly it abrogated PPC induced cardiac protection. Finally, PPC induced protection and blockade of locally produced Ang II involved enhanced activation of ERK1/2 and Akt. Conclusions: This study demonstrate a novel interaction between PPC mediated cardiac protection and ACE-Ang II-AT1 axes of the RAS in which locally produced Ang II appears to play a significant role in PPC mediated protection while systemically produced Ang II appears to be dispensable. Moreover this interactions appears to involve alterations in the activation state of downstream kinases including ERK1/2 and Akt. Acknowledgement: This study is supported by grant number MY 02/10 from Research Administration, Kuwait University, Kuwait.